2018
DOI: 10.1292/jvms.17-0512
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic and cardiorespiratory effects of single-bolus intravenous alfaxalone with or without intramuscular xylazine-premedication in calves

Abstract: The anesthetic and cardiorespiratory effects of xylazine-alfaxalone combination were evaluated in calves. Six calves (age: 6–9 months old; weight: 114–310 kg) were anesthetized with intravenous alfaxalone 15 min after administration of intramuscular saline (0.5 ml/100 kg) or xylazine (0.1 mg/kg; 0.5 ml/100 kg of a 2% xylazine solution). Anesthesia induction was smooth and orotracheal intubation was achieved in all calves. The calves anesthetized with xylazine-alfaxalone required a smaller induction dose of alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Another study revealed that increased HR was possibly induced via an activating effect of alfaxalone on sympathetic outflow [ 34 ]. The f R remained unchanged in goats administered alfaxalone alone, but those receiving xylazine and alfaxalone exhibited mild depression in ventilation rate that was considered clinically insignificant [ 15 , 35 ]. In prior reports, anesthesia induction with propofol, ketamine or thiopental revealed a decrease in blood pressure, f R and mild increase in HR as well as hypothermia in goats [ 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that increased HR was possibly induced via an activating effect of alfaxalone on sympathetic outflow [ 34 ]. The f R remained unchanged in goats administered alfaxalone alone, but those receiving xylazine and alfaxalone exhibited mild depression in ventilation rate that was considered clinically insignificant [ 15 , 35 ]. In prior reports, anesthesia induction with propofol, ketamine or thiopental revealed a decrease in blood pressure, f R and mild increase in HR as well as hypothermia in goats [ 28 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The drug has brought abrupt changes in the cardiopulmonary function including a reduction in the heart rate, respiratory rate, and cardiac output and inducing fluctuation of blood pressure and oxygen tension. These changes have been selectively studied through intra-arterial catheterization, blood gas analysis, M-mode echocardiography, and electrocardiography in different animal species including cattle [24], donkey [25,26], calves [27,28], and goats [29,30]. As far as we concern, exploration of animal models may require anesthesia, but under farm conditions, the effect of short-term tranquilization with xylazine on quantitative echocardiography measurement was not previously studied in goats.…”
Section: Introductionmentioning
confidence: 99%
“…Undesirable issues during recovery, such as nausea, vomiting, ataxia, muscle tremors, opisthotonus-like postures, pronounced limb extension, and paddling were reported to some extent in many animal species receiving intravenous (IV) or IM administration of alfaxalone-HPCD alone [ 8 , 10 , 12 , 13 , 18 , 24 , 25 ]. Tamura et al [ 24 ] observed ataxia, tremors, and opisthotonus-like postures during the early recovery period after administration of IV alfaxalone-HPCD at 5 mg/kg, as well as after using IM alfaxalone-HPCD at 2.5, 5, and 10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Tamura et al [ 25 ] considered the qualities of recovery from IM alfaxalone-HPCD at 5, 7.5, and 10 mg/kg to be satisfactory in dogs, but all the dogs in this study still exhibited transient muscular tremors and staggering gaits. In addition, tremors, paddling, seizure-like activity, and thrashing were observed during the recovery period in alpacas [ 8 ] and calves [ 10 ], which were anesthetized with IV alfaxalone-HPCD alone. Huynh et al [ 12 ] reported that the recovery from IM alfaxalone-HPCD at 4, 6, and 8 mg/kg was uneventful in rabbits except for one animal that died 10 min after an IM injection of 8 mg/kg.…”
Section: Discussionmentioning
confidence: 99%